Math for business and finance : an algebraic approach / Jeffrey Slater, North Shore Community College, Danvers, Massachusetts, Sharon M. Wittry, Pikes Peak Community College, Colorado Springs, Colorado. - Slater, Jeffrey,1947-author.
Includes index.